Evolution of viral DNA-dependent RNA polymerases - Sonntag, Kai-Christian; Darai, Gholamreza (Virus genes, 1995)
The DNA-dependent RNA polymerase (DdRP or RNAP) is an essential enzyme of transcription of replicating systems of prokaryotic and eukaryotic organisms as well as cytoplasmic DNA viruses. DdRPs are complex multisubunit enzymes consisting of 8-14 subunits, including two large subunits and several smaller polypeptides (small subunits). An extensive search between the amino acid sequences of the known largest subunit of DNA-dependent RNA polymerases (RPO1) of different organisms indicates that all these polypeptides possess auniversal heptapeptideNADFDGD in domain D. All RPO1 harbor a second well-conserved hexapeptideRQP(TS)LH upstream (26-31 amino acids) of the universal motif. The genes encoding the largest subunit of DdRP of insect iridescent virus type 6 (IIV6), fish lymphocystis disease virus (LCDV), and molluscum contagiosum virus (MCV-1), all members of the group of cytoplasmic DNA viruses, were identified by PCR technology. With the exception of IIV6, all other viral RPO1 possess the two C-terminal conserved regions G and H. The lack of C-terminal repetitive heptapeptide (YSPTSPS), which is a common feature of the largest subunit of eukaryotic RNAPII, is an additional characteristic of RPO1 proteins of LCDV and of MCV-1. All viral RPO1 proteins were found to be lacking the amino acid N at a distinct position in domain F. This amino acid is known to be highly conserved in α-amanitin-sensitive eukaryotic RNA polymerases II. Comparison of the amino acid sequences of the RPO1 polypeptides of IIV6, LCDV, and MCV-1 with the corresponding prokaryotic, eukaryotic, and viral proteins revealed differences in amino acid similarity and phylogenetic relationships. IIV6 RPO1 possesses the closest similarity to the homologous subunit of eukaryotic RNAPII and lower but also significant similarity to that of eukaryotic RNAPI and RNAPIII, archaeal, eubacterial, and viral polymerases. The similarity between RPO1 of IIV6 and the cellular polymerase subunits is consistently higher than to the RPO1 of other cytoplasmic DNA viruses, for example, vaccinia and variola virus, African swine fever virus (ASFV), and MCV-1. The RPO1 of LCDV shows the highest similarity to the RPO1 of IIV6 and significant lower similarity to the eukaryotic polymerases II and III as well as to the archaebacterial subunit. However, it is still considerably more similar to the cellular polymerase subunits than to the homologous viral proteins. The RPO1 of IIV6 possesses more similarity to cellular polymerases than the complete RPO1 of LCDV, indicating that there is a substantial difference in the organization of the RPO1 genes between these members of two genera of the Iridoviridae family. Analysis of the MCV-1 RPO1 revealed high amino acid homologies to the corresponding polypeptides of vaccinia and variola virus. The viral RPO1 proteins, including vaccinia and variola virus, MCV-1, ASFV, IIV6, and LCDV, share the common feature of showing the highest similarity to the largest subunit of eukaryotic RNAPII than to that of RNAPI, RNAPIII, and RPO1 of archaebacterias, eubacterias, ASFV, IIV6, and LCDV. Evolution of the individual largest subunit of DdRPs was tentatively investigated by generating phylogenetic trees using multiple amino acid alignments. These indicate that the RPO1 proteins of IIV6 and LCDV might have evolved from the largest subunit of eukaryotic RNAPII after divergence from the homologous subunits of RNAPI and RNAPIII. In contrast, evolutionary development of the RPO1 of vaccinia and variola virus, MCV-1, and ASFV seems to be quite different, with their common ancestor diverging from cellular homologues before the separation of the three types of eukaryotic polymerases and having probably diverged earlier from their common lineage with cellular proteins.